International workshop on Crassulacean acid metabolism, held at Smithsonian Tropical Research Institute, Republic of Panama, March 21-26, 1993 - Klaus Winter (Springer-Verlag, 1996)
The book begins with summary of the basic priciples of CAM to lay the foundations for three major sections that cover the different areas of current research: Part A deals with the biochemistry of the CAM cycle; Part B focuses on the environmental and developmental control of CAM and underlying molecular mechanisms; Part C is devoted to the ecological diversity and evolutionary origins of CAM